Restorative Justice in the Indonesian Criminal Justice System: An Analysis of the Normative Construction of the Criminal Code and the Criminal Code in the Perspective of Pancasila and Legal Reform - Muhammad Rifaid; Syamsuddin; Ridwan; Hajairin; Musmuliadin (Lembaga Bale Literasi, 2025)
Through legal doctrinal research, this paper investigates the normative construction and philosophical foundations of integrating restorative justice in the Indonesian criminal justice system. This study uses legislative, comparative, and conceptual methods to assess the legal structure, consistency, and prospects for the implementation of the National Criminal Code (Law No. 1/2023) and the Criminal Procedure Law (Kitab Undang-Undang Hukum Acara Pidana/KUHAP). The results of the study show a fairly comprehensive normative framework with a strong philosophical foundation based on Pancasila, supported by constitutional clauses and customary law traditions. In particular, this study found that the paradigm transformation from retributive to restorative is reflected in the goal of punishment that emphasizes the restoration of social relationships, the reintegration of perpetrators, and the protection of victims. However, the effectiveness of implementation still faces challenges in the form of regulatory disharmony, limited capacity of law enforcement officials, and the lack of optimal monitoring and evaluation mechanisms for the implementation of restorative agreements. In addition, there are normative gaps related to loss recovery standards, protection of vulnerable groups, and integration of customary law in formal judicial practice. This condition shows that although conceptually restorative justice has acquired strong normative legitimacy, its implementation still requires institutional strengthening and policy harmonization. To ensure effective, equitable, and protection-oriented implementation of human rights, this study proposes a framework for the Pancasila-Based Integrated Restorative Justice System and offers legal policy recommendations that emphasize the integration of structural, substantial, cultural, and procedural dimensions in the national criminal justice system.